Enhancing ICU Candida spp. surveillance : a cost-effective approach focused on Candida auris detection - Nascimento, Teresa (2024)
Introduction: Candida auris is an emerging pathogen that represents a worldwide health problem due to its global expansion, multidrug resistance, and difficult laboratory identification. Among the risk factors for colonization/infection by C. auris, a stay in an intensive care unit (ICU) stands out. This prospective multicenter study aimed to monitor the trend of the local epidemiology of Candida spp. and unveil the prevalence of C. auris. Methods: From 2020 to 2022, axillar/inguinal swabs were collected from adult patients at three points: upon admission (D1) and on the fifth (D5) and eighth (D8) days of their ICU stay. We employed culture-based screening methods combined with molecular techniques to identify Candida spp. down to the species level. Specific screening for Candida auris was conducted using a real-time PCR assay in combination with an improved selective culture medium, mannitol salt agar auris (MSAA). To validate the effectiveness of MSAA, a collection of reference C. auris strains representing the four major geographical clades was used. Results: We enrolled 675 patients, and 355 Candida isolates were retrieved from the 988 swab samples collected. From those, 185/355 (52.1%) were identified as C. albicans and 170/355 (47.9%) as non-albicans Candida (NAC). MSAA medium showed a specificity of 94.8%, albeit C. auris was not detected in this cohort. The dynamics of Candida spp. colonization by ICU were significant at the three collection points. Upon admission, C. albicans was associated with the Beatriz Ângelo Hospital ICU (p=0.003) and C. tropicalis with the general Hospital Professor Doutor Fernando Fonseca (FFH) ICU (p=0.006). C. parapsilosis and C. lusitaniae were associated with FFH ICUs, with the general ICU at D5 (p=0.047) and surgical ICU at D8 (p=0.012). The dynamics of NAC colonization by ICU were significantly different at D1 (p=0.011), D5 (p=0.047), and D8 (p=0.012). Conclusion: We developed and implemented a screening protocol for C. auris while uncovering the colonization patterns of Candida in the ICU. Our findings contribute to the optimization of overall patient management, ensuring that ICU protocols are resilient and adaptive to emerging fungal threats.